Responsibility and Sanction on Accountable Governance in the Procurement of Goods and Services of the Teluk Bintuni Regency Government - Kristiono, Hellyn (KnE Social Sciences, 2025)
Public procurement of goods and services is intended to enable the government to fulfill its obligation to provide public infrastructure. Accountability stipulates that every activity and the final result of government administration activities through the public bureaucracy must be accountable to the public. This study aims to analyze responsibility and sanction in accountable governance for the procurement of goods and services in the Teluk Bintuni Regency Government. This research used a qualitative approach. Data collection methods include observation, in-depth interviews, and documentation. Data sources consist of primary data and secondary data. The informants in this research are stakeholders who are directly involved in the procurement of goods and services. The results of this study indicate that the procurement of goods and services in Southwest Papua Province has not been fully effective. This is because the responsibility dimension in the procurement of goods and services shows that there are limited competencies and understanding of regulations in the Regional Work Unit, delays in the procurement process, lack of coordination and commitment, lack of community participation, limited access to information, and limited capacity to report irregularities. Meanwhile, the action dimension shows that in reporting and complaints, there is a lack of protection for whistleblowers and a lack of understanding and socialization related to reporting and complaints;the reporting process is a challenge for people who do not have access and capacity.